2005
DOI: 10.1590/s0034-70942005000500006
|View full text |Cite
|
Sign up to set email alerts
|

Disfunção cognitiva pós-operatória: prevalência e fatores associados

Abstract: RESUMO U n i t e r m o s : C O M P L I C A Ç Õ E S : d i s f u n ç ã o c o g n i t i v a pós-operatória SUMMARY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
(6 reference statements)
0
8
0
2
Order By: Relevance
“…In most of the studies different methods of neuropsychological testing were implemented, including MMSE [ 29 , 34 , 35 , 36 ], various batteries of popular neuropsychometric tests (for example, Williams-Russo [ 28 ] used a battery of 10 tests, Panda [ 31 ] 7 tests and Moller [ 12 ] 4 different tests) and some self-developed ones (Heyer et al [ 32 ]). Such diversity and lack of standardization impedes the drawing of reliable conclusions and does not allow to formulate recommendations for clinicians for several reasons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In most of the studies different methods of neuropsychological testing were implemented, including MMSE [ 29 , 34 , 35 , 36 ], various batteries of popular neuropsychometric tests (for example, Williams-Russo [ 28 ] used a battery of 10 tests, Panda [ 31 ] 7 tests and Moller [ 12 ] 4 different tests) and some self-developed ones (Heyer et al [ 32 ]). Such diversity and lack of standardization impedes the drawing of reliable conclusions and does not allow to formulate recommendations for clinicians for several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…The sole fact that different BP thresholds were applied appears to be a barrier for effective complex analysis. Only 6 out of 13 studies described IOH as either a direct value [ 28 , 34 , 36 , 37 ] or a relative BP drop [ 12 , 29 ]. Additionally, the definitions varied in their established minimal threshold for IOH duration, ranging from the very moment of IOH occurrence to even ≥30 min.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with the findings in the present study. The MMSE is widely utilized in research on preoperative cognitive function, and some studies reported that a low preoperative MMSE was a predictor of postoperative delirium 2 , 6 , 29) . Although the MMSE is a convenient and easy method to assess a patient's cognitive function, repeated MMSEs over short time intervals are not recommended because of the learning effect 8 , 34) .…”
Section: Discussionmentioning
confidence: 99%
“…The other three studies determined the incidence of POCD using MMSE scale. POCD was defined if the difference between post- and preoperative MMSE score was equal or larger than the standard deviation of preoperative MMSE scores [30]. …”
Section: Resultsmentioning
confidence: 99%